Who's hanging out and what's happening? A look at the interplay between unstructured socializing, crime propensity and delinquent peers using social network data. (January 2018) - Gerstner, Dominik; Oberwittler, Dietrich
One of the key observations of delinquency research – that adolescents are more likely to offend during the time spent in the company of peers and without adult supervision – has been supported by recent studies following Situational Action Theory (SAT). According to SAT, exposure to criminogenic settings may influence adolescent behaviour by presenting opportunities and frictions; however, the outcome is seen as conditional on individual crime propensities and the moral context in which opportunities and frictions are encountered. To what extent the behaviour of adolescents in these settings also depends on the delinquent inclinations of their peers is an additional question that has received less attention. In the current study, we use data from a recent German school survey, including network data and a direct measurement of delinquent friends, to test for interactions between unstructured socializing and the crime propensities of respondents, as well as of their friends, and find support for SAT. In this context the measurement of 'delinquent friends' becomes important because its association with an adolescent's own delinquency is likely to be overestimated when respondents report on their friends' behaviour. The novel contribution of this study is to analyse how the interplay between these factors changes if one moves from an indirect to a direct measurement of friends' delinquency. We show that the influence of situations and opportunities is unduly diminished when using the indirect measurement.